2017
DOI: 10.1039/c7cp04056c
|View full text |Cite
|
Sign up to set email alerts
|

The borazine dimer: the case of a dihydrogen bond competing with a classical hydrogen bond

Abstract: Dimers of borazine were studied using matrix isolation infrared spectroscopy and ab initio quantum chemical calculations. Computations were performed at the MP2 and M06-2X levels of theory using the 6-311++G(d,p) and aug-cc-pVDZ basis sets for the various homodimers. At both levels of theory, an aligned stacked structure was found to be the global minimum, which was nearly isoenergetic to a parallel displaced structure. A T-shaped structure, where the N-H of one borazine pointed towards the N of the second bor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 47 publications
0
17
0
Order By: Relevance
“…No experimental study on the B 3 N 3 H 6 ‐C 6 H 6 heterodimer has been reported so far. In this work, we have explored the B 3 N 3 H 6 ‐C 6 H 6 heterodimers using matrix isolation infrared experiments and ab initio computations and have drawn a comparison between our previously studied B 3 N 3 H 6 dimer, the well studied C 6 H 6 dimer and the heterodimer of B 3 N 3 H 6 and C 6 H 6 addressed in this work . Our experimental studies on the B 3 N 3 H 6 homodimers revealed the aligned stacked structure to be the global minimum.…”
Section: Introductionmentioning
confidence: 58%
See 4 more Smart Citations
“…No experimental study on the B 3 N 3 H 6 ‐C 6 H 6 heterodimer has been reported so far. In this work, we have explored the B 3 N 3 H 6 ‐C 6 H 6 heterodimers using matrix isolation infrared experiments and ab initio computations and have drawn a comparison between our previously studied B 3 N 3 H 6 dimer, the well studied C 6 H 6 dimer and the heterodimer of B 3 N 3 H 6 and C 6 H 6 addressed in this work . Our experimental studies on the B 3 N 3 H 6 homodimers revealed the aligned stacked structure to be the global minimum.…”
Section: Introductionmentioning
confidence: 58%
“…Furthermore, since these features were observed even at low concentrations of benzene and borazine (trace ‘d’), they must be due to 1:1 complexes. The features at 3462.8 and 3458.0 shown in trace (c) and (d) correspond to the B 3 N 3 H 6 homodimers, which has been reported earlier …”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations